General Risk on Trust, Satisfaction, and Recommendation Intention for Halal Food`: Evidence in Indonesia - Amelia Tri Puspita; Anwar Adem Shikur (SMART Insight, 2022)
The purpose of this empirical research is to determine the effect of multidimensional general risk factors on halal consumer confidence, satisfaction, and intention to recommend halal food. This study also calculates the average comparison of trust, satisfaction, and recommendation intentions across demographic variables of halal customers. Our results from structural analysis reveal that general risks have a significant and positive effect on trust, satisfaction, and intention to recommend halal food. Also, the results of the mean difference test show that satisfaction and intention to recommend halal food differ significantly between male and female customers and trust varies significantly among halal customers with different educational backgrounds and marital status. This study adds a valuable contribution to the current literature on halal food consumption by undertaking a series of symmetrical analytical approaches to assess the desired responses from halal food customers.